Determinant Environment Disclosures of Public Listed Firms in Malaysia - Mohd Waliuddin, Mohd Razali; Samuel Ching Lee, Tu; Josephine, Yau Tan Hwang; Sharifah Sabrina, Syed Ali (2022)
Environmental activities disclosure has been addressing many stakeholders until now due the effect climate change and natural ecological system. The aim of this study is to examine the relationship between firm characteristics and environmental disclosure. Final sample of this study consist 442 Malaysian listed firms period of 2016. All numerical data to measure variables such firm size, profitability, leverage and disperse share ownership were obtain from Eikon database while dependent variable which is environmental disclosure and other variables such as environmental management systems (EMS), age and auditor type were obtain from published firm annual reports. The results show that all variables significant influence environmental disclosure except leverage and auditor type. Future studies suggest that using other proxies of environmental disclosure and independent variables such as foreign association, brand awareness, firm value and cost of financing that could give new insight to the environmental disclosure practice.